2007
DOI: 10.1179/174329407x215159
|View full text |Cite
|
Sign up to set email alerts
|

Adhesion tests for thermal spray coatings: Correlation of bond strength and interfacial toughness

Abstract: In this paper, experiments for determining the adhesion properties have been performed using two test methods; tensile adhesive test which is widely used in industry and interfacial indentation test still under development in research laboratories. Therefore, only few experimental data on the accuracy of the methods and on the potential in an industrial context are available. For that reason, dissimilar coating-substrate combinations covering different ranges of type of thermal spray coating-substrate systems … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
28
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(28 citation statements)
references
References 19 publications
0
28
0
Order By: Relevance
“…For scanning profilometers a typical data set has lateral step size of the data points between 1 and 100 lm. The typical total number of data points is about 10 5 . SM images and data sets contain several 10 6 data points.…”
Section: Advantages and Constraints Of Smmentioning
confidence: 99%
See 1 more Smart Citation
“…For scanning profilometers a typical data set has lateral step size of the data points between 1 and 100 lm. The typical total number of data points is about 10 5 . SM images and data sets contain several 10 6 data points.…”
Section: Advantages and Constraints Of Smmentioning
confidence: 99%
“…An important issue for the successful application of such coatings is the control of the roughness of the substrate as well as of the coating. For good adhesion between the sprayed coating and the substrate, an optimal substrate surface topography is often needed (Ref 4,5). For medical implants the surface morphology and roughness on different length scales must be optimized for good adhesion of cells (Ref 6).…”
Section: Introductionmentioning
confidence: 99%
“…Previous tensile adhesion tests of APS and high-velocity oxyfuel sprayed TBC systems have shown that TBC systems mainly fracture close to the BC/TC interface and give adhesion strengths of 10-50 MPa, [34][35][36][37]. Fracture toughness measurement by Vickers indentation has also been shown applicable to coatings, [27,36,38,39], and a correlation has been found between tensile adhesion strength and interface indentation toughness, [27,36]. Tensile adhesion of heat treated coatings has been somewhat studied, [31,34,39,40]: TBC systems exposed to short, (2 h), heat treatments exhibited an increase in adhesion strength, [34], while thermal cycling decreased the adhesion strength, [40].…”
Section: Introductionmentioning
confidence: 99%
“…Several methods are available for evaluating the adhesion of TBCs, [27][28][29][30][31][32][33]. One of them, and the one of concern in the present study, is the tensile adhesion test (TAT) described in ASTM C633, according to which one uses a common tensile test machine to measure the adhesive strength of a TBC system.…”
Section: Introductionmentioning
confidence: 99%
“…This effect is called an "anchoring effect", which is particularly well known in the field of anti-corrosive coatings, heat resistant coatings, and designable coatings. The anchoring effect improves lubricant performance for properties such as corrosion resistance, adhesion strength, and long-term sustainability of various functional properties [4][5][6].…”
Section: Introductionmentioning
confidence: 99%